Analysis of earthquake impact on market buildings in North Bengkulu using the soil response and finite element method - Anugrah Juniarto, Danu; Lindung Zalbuin Mase; Khairul Amri; Rena Misliniyati; Fepy Supriani (Teknisia, 2026)
The vulnerability of market buildings in active seismic zones, such as North Bengkulu which is surrounded by the Sumatran subduction zone and active faults presents a critical research challenge due to the lack of integrated soil-structure seismic assessments for commercial infrastructure. The aim of this study is to evaluate the effects of earthquakes on the Purwodadi Market Building through the integration of soil response analysis and structural dynamics. The methods employed involved calculating soil response based on historical earthquake records of the 2007 Bengkulu–Mentawai Earthquake (subduction, Mw 8.4) and the 1952 Ketahun Earthquake (active fault, Mw 6.8), followed by structural modelling using the Finite Element Method (FEM). The main quantitative results show that the local clay layer significantly amplifies ground motion, with a Peak Ground Acceleration (PGA) at the surface of 0.485 g for the subduction earthquake and 0.389 g for the fault earthquake. The amplification factors at the surface are 1.95 and 1.73, respectively. Structural simulations recorded a substantial increase in internal forces; for example, the bending moment in beam B1 increased from 0.82 kNm to 61.01 kNm, and the shear force at the head of the pile cap PC increased from 2.15 kN to 65.12 kN. Nevertheless, all structural components maintained stress ratios below 1.0, confirming that the building meets the safety standards of SNI 1726:2019. It is concluded that the integration of site-specific ground response with FEM-based structural dynamics is crucial for improving seismic resistance assessment. This study recommends the continued application of this combined method for buildings in earthquake-prone areas and the expansion of earthquake data coverage to improve future risk mitigation strategies.